2014
DOI: 10.1111/tri.12264
|View full text |Cite
|
Sign up to set email alerts
|

High-mobility group box 1 accelerates early acute allograft rejection via enhancing IL-17+γδ T-cell response

Abstract: SummaryTh17 and cd T cells are the dominant IL-17-producing cell. We previously reported that high-mobility group box 1 (HMGB1) is critical in inducing IL-17-producing alloreactive T cells during early stage of acute allograft rejection. However, the role of cd T cells during this process and its implication in HMGB1-mediated allograft rejection are not fully understood. Here, we use a murine model of cardiac allograft transplantation to further study the role of HMGB1 and IL-17-producing cd T cells in acute a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Our previous studies have also demonstrated that HMGB1 plays critical roles in the pathogenesis of acute allograft rejection (16,17,19). This recent discovery of the extracellular role of HMGB1 as a proinflammatory cytokine has opened up a new field of research to study the role of HMGB1 in chronic allograft rejection.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Our previous studies have also demonstrated that HMGB1 plays critical roles in the pathogenesis of acute allograft rejection (16,17,19). This recent discovery of the extracellular role of HMGB1 as a proinflammatory cytokine has opened up a new field of research to study the role of HMGB1 in chronic allograft rejection.…”
Section: Discussionmentioning
confidence: 93%
“…Monoclonal anti-HMGB1 neutralizing antibody (isotype IgG) derived from NZB/W mouse (HMGB1 Ab) (19,23,24) was gifted by the Institute of Biophysics, Chinese Academy of Science (Beijing, China). Of HMGB1 Ab, 200 mg were injected into recipient intraperitoneally (i.p.…”
Section: Hmgb1 Antibody Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we detected the nuclear expression of HMGB1 in some of astrocytes, microglia and a few neurons in adult mouse spinal cord, which supplies more information to characterize the expression of HMGB1 in CNS and helps in discovering the potential CNS specific functions of HMGB1. Extracellular HMGB1, which is released passively by death cells or actively by stimulated cells such as macrophages, has been reported to play a key role in autoimmune diseases (Magna and Pisetsky, 2014), allograft rejection (Xia et al, 2014), ischemic stroke (Hayakawa et al, 2012), traumatic brain injury (Laird et al, 2014), and neurodegenerative diseases (Fang et al, 2012) as an inflammatory mediator. MS/EAE is a CNS specific autoimmune disease, which happens in adult human being or is induced in adult animal.…”
Section: Discussionmentioning
confidence: 99%